2011
DOI: 10.1097/ccm.0b013e31821867cc
|View full text |Cite
|
Sign up to set email alerts
|

Nursing considerations to complement the Surviving Sepsis Campaign guidelines

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link Financial supportThis project was conducted under the auspices of the World Federation of Critical CareNurses (WFCCN), and no sponsorship or funding was received for this project. NURSING CONSIDERATIONS TO COMPLEMENT THE SURVIVING SEPSIS CAMPAIGN GUIDELINES ABSTRACTObjective: To provide a series of recommendations, based on the best available evidence, to guide cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 229 publications
(194 reference statements)
0
32
0
5
Order By: Relevance
“…Infection prevention measures relate to accountability, education, surveillance of nosocomial infection, hand hygiene, and prevention of respiratory, central catheter-related, surgical site, and urinary tract infections. 17 Although the literature indicates that the incidence of antimicrobial resistance does not change appreciably with current selective digestive decontamination regimens, [18][19][20] the use of oral chlorhexidine gluconate is relatively easy, decreases the risk of nosocomial infection, and reduces potential concern over promotion of antimicrobial resistance by selective digestive decontamination regimens. …”
Section: Infection Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection prevention measures relate to accountability, education, surveillance of nosocomial infection, hand hygiene, and prevention of respiratory, central catheter-related, surgical site, and urinary tract infections. 17 Although the literature indicates that the incidence of antimicrobial resistance does not change appreciably with current selective digestive decontamination regimens, [18][19][20] the use of oral chlorhexidine gluconate is relatively easy, decreases the risk of nosocomial infection, and reduces potential concern over promotion of antimicrobial resistance by selective digestive decontamination regimens. …”
Section: Infection Preventionmentioning
confidence: 99%
“…In addition, oropharyngeal decontamination with oral chlorhexidine gluconate is suggested to reduce the risk of ventilator-associated pneumonia in ICU patients with severe sepsis (grade 2B). 1 An outline of infection prevention measures as a prime area of focus of nursing care in patients at risk for infection potentially leading to sepsis has been provided in "Nursing Considerations to Complement the surviving sepsis Campaign," 17 the companion document to the 2008 surviving sepsis Campaign guidelines. Critically ill patients are at high risk of acquiring a hospital-associated infection because of the presence of invasive catheters and tubing, drains and tubes, wounds, and other complex therapies they receive.…”
Section: Infection Preventionmentioning
confidence: 99%
“…Endotracheal suctioning (if necessary) hurts, prolonged immobilization and routine care are painful, and general intense discomfort of vague origin is common in critical illness; 19,20 pain is one of major issue in sepsis and requires a continuous monitoring; 8 v) observing the patient: to perform halfhourly observations of vital signs and hourly measurement of urinary output; 5,7 vi) considering patient and family comfort/care: to promote patient comfort/pain relief/sedation/turning/skin care; provide patient and family teaching; address needs of families of critically ill patients. 2 We can also consider these recommendations like the interventions for the main nursing diagnoses identified in patients with sepsis in 2014: 21 the main nursing diagnoses, described according to the NANDA-I taxonomy are: risk for infection, risk for aspiration, risk for impaired skin integrity, impaired skin integrity, impaired spontaneous ventilation, impaired gas exchange.…”
Section: 2mentioning
confidence: 99%
“…Expert nurses with advanced skills are needed to identify patients with deterioration of clinical status and to ensure appropriate assistance to patients with sepsis. 2 A study performed in 2011, 2 identified sixty-three recommendations to guide clinical nurses who care for patients with sepsis. The macro subjects are: -Prevention of infection: the subject is education of staff which happens to be the first step (fundamental) to raise awareness of the problem and implement strategies for preventing infection, the accountability which results in the promotion of a culture of patient safety, the continuous surveillance of nosocomial infections, washing hands as evidence suggests that a proper hand washing reduces the rate of infections or alternatively the use of hydro-alcoholic gel and the proper use of those devices that can be vehicles of infection (e.g., mechanical ventilation patients, venous catheter-related infections, surgical-site infections and urinary tract infections).…”
Section: Nursing Management Of Septic Patientmentioning
confidence: 99%
“…[58][59][60][61] It has been hypothesized, however, that semirecumbent positioning puts patients at risk for pressure ulcers. In an open, prospective, randomized cross-over trial, the interface pressure was measured over distinct body positions by using a pressure-mapping device.…”
Section: Pressure Ulcersmentioning
confidence: 99%